Psychopathy : antisocial, criminal, and violent behavior - Millon, Theodore (Guilford, 1998)
I: History and viewpoints * Historical conceptions of psychopathy in the United States and Europe / Theodore Millon, Erik Simonsen and Morten Birket-Smith * Psychopathy: An elusive concept with moral overtones / John Gunn * Personality and crime / H. J. Eysenck * Psychopathy and the contribution of personality to violence / Ronald Blackburn * Evil intent: Violence and disorders of the will / Henry Richards * The internal world of the psychopath / J. Reid Meloy and Carl B. Gacano * Antisocial character and behavior: Threats and solutions / William H. Reid * The case for parental licensure / David T. Lykken * Psychopathy or antisocial personality in forensic settings / Hans Toch II: Typologies * Ten subtypes of psychopathy / Theodore Millon and Roger D. Davis * Psychopathy and the five-factor model of personality / Thomas A. Widiger and Donald R. Lynam * Psychopaths and their nature: Implications for the mental health and criminal justice systems / Robert D. Hare III: Etiology * Genetics and antisocial personality disorder / Peter McGuffin and Anita Thapur * Neurobiology in psychopathy / Larry J. Siever * Psychopathic children: Indicators of organic dysfunction / Niels Peter Rygaard * Cross-cultural aspects of psychopathy / David J. Cooke * A biopsychosocial model of psychopathy / Joel Paris IV: Comorbidity * Psychopathy and psychiatric comorbidity / Alv A. Dahl * Psychopathy in the pedophile / Darwin Dorr * Comorbidity of alcoholism and psychopathy / Joachim Knop, Per Jensen and Erik Lykke Mortensen * Antisocial personality disorder and narcotic addiction / Per Vaglum * Sadistic personality in murderers / Michael H. Stone V: Treatment * Psychopharmacological treatment and impulsivity / Lars von Knorring and Lisa Ekselius * The psychotherapeutic management of psychopathic, narcissistic, and paranoid transferences / Otto F. Kernberg * A group-analytic approach to psychopaths: "The Ring of Truth" / Murray Cox * Therapeutic community treatment for severe personality disorders / Bridget Dolan * The management of dangerous psychopaths in prison / Jeremy W. Coid * Treating the "untreatable" in Denmark: Past and present / Heidi Hansen